2012
DOI: 10.1097/qai.0b013e31826249cf
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Sequencing of the V3-loop Can Predict the Virological Response to Maraviroc in Treatment-Naive Patients of the MERIT Trial

Abstract: The exclusion of ∼8% of patients with CXCR4-using virus by population-based sequencing would likely have resulted in noninferior responses in the MVC twice-daily and EFV arms. Rescreening by ESTA and population-based sequencing predicted similar virological response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…Of the clonal model 5.75% FPR was first selected as this is the only validated FPR with clinical studies. 31,32 ''Recommendations from the European Consensus Group on the clinical management of HIV-1 tropism testing (10% FPR)'' 3 was selected for the second batch of analysis. The third set of analysis used the clinical model of G2P (FPR = 10%) 10,33 with the input of patient clinical parameters including viral load and CD4 and CD8 cell counts.…”
Section: Tropism Genotyping By G2p Webpssm and Cn Rulesmentioning
confidence: 99%
“…Of the clonal model 5.75% FPR was first selected as this is the only validated FPR with clinical studies. 31,32 ''Recommendations from the European Consensus Group on the clinical management of HIV-1 tropism testing (10% FPR)'' 3 was selected for the second batch of analysis. The third set of analysis used the clinical model of G2P (FPR = 10%) 10,33 with the input of patient clinical parameters including viral load and CD4 and CD8 cell counts.…”
Section: Tropism Genotyping By G2p Webpssm and Cn Rulesmentioning
confidence: 99%
“…The position-specific scoring matrix (PSSM) analyzes the entire V3 sequence and predicts X4 variants based on a scoring of the probability of the amino acid at each position being overrepresented among X4 sequences versus R5 sequences (10). The Geno2Pheno (G2P) algorithm (11) also analyzes the entire V3 sequence and provides a quantitative score (false-positive rate [FPR]) representing the probability of falsely predicting an R5 variant as an X4 variant; the validity of this approach has been assessed in several clinical trials (12)(13)(14)(15)(16). G2P has been widely used in research and clinical settings, but it requires a preset FPR cutoff to call X4 variants.…”
mentioning
confidence: 99%
“…A retrospective study evaluated genotypic tropism testing using stored plasma samples collected in the maraviroc trials and found that it was comparable to the original Trofile assay in predicting virological outcomes in treatment-experienced patients [38 ]. These authors drew the same conclusions in a study of treatmentnaive patients [39]. Genotypic tropism testing is also possible from proviral DNA, indicating a use in patients with a suppressed viral load, who are seeking to switch treatment for tolerability reasons [40,41].…”
Section: Tropism Testingmentioning
confidence: 95%